Nitrogen metabolism of Aspergillus and its role in pathogenicity - Krappmann, S; Braus, G H (Medical mycology (Oxford), 2005)
Aspergilli represent unique pathogens. Based on their saprophytic life style they are able to colonize a variety of ecological niches, among them the immunocompromised individual. Distinct fungal attributes that play a role in pathogenicity of aspergilli have been described, and primary metabolism indisputably has to be taken into account for contributing to the virulence potential of this fungal genus. Here we present an overview of studies that focus on this aspect of nutritional versatility. In the predominant pathogenic representative Aspergillus fumigatus regulation of nitrogen utilization and sensing of nitrogen sources have been scrutinized with respect to pathogenicity. The impact of distinct metabolic pathways on virulence capacities could be evaluated by inspection of auxotrophic mutant strains. Among them, para-aminobenzoic acid-requiring mutants revealed that this biosynthetic route is strictly required for pathogenicity. For amino acid anabolism only lysine biosynthesis has been investigated in this regard. Fungal amino acid biosynthesis is generally subject to strict regulation mediated by the Cross-Pathway Control system, a conserved regulatory circuit evolved to counteract conditions of nutritional stress. A clear influence of the system on pathogenicity could be observed by targeting its transcriptional activator CpcA. However, additional metabolic characteristics as well as regulatory instruments that compensate environmental challenges need to be addressed in future research with the aim to assess the significance of fungal primary metabolism for pathogenicity of aspergillus species.